1995
DOI: 10.1105/tpc.7.9.1357
|View full text |Cite
|
Sign up to set email alerts
|

Disease resistance conferred by expression of a gene encoding H2O2-generating glucose oxidase in transgenic potato plants.

Abstract: Plant defense responses to pathogen infection involve the production of active oxygen species, including hydrogen peroxide (H2O2). We obtained transgenic potato plants expressing a fungal gene encoding glucose oxidase, which generates H2O2 when glucose is oxidized. H2O2 levels were elevated in both leaf and tuber tissues of these plants. Transgenic potato tubers exhibited strong resistance to a bacterial soft rot disease caused by Erwinia carotovora subsp carotovora, and disease resistance was sustained under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(84 citation statements)
references
References 47 publications
6
73
0
5
Order By: Relevance
“…The presence of horseradish peroxidase (and H202) was required for cross-linking to occur (data not shown). The relatively high catalase concentration is consistent with that used in previous studies (Behl et aL, 1994;Levine et al, 1994;Wu et al, 1995) and reflects the high K m of the enzyme. The water fractions were solubilized for 15 min at 22°C in sample buffer (Laemmli, 1970) and resolved by SDS-AGE.…”
Section: In Vitro Agp Cross-linkingsupporting
confidence: 89%
“…The presence of horseradish peroxidase (and H202) was required for cross-linking to occur (data not shown). The relatively high catalase concentration is consistent with that used in previous studies (Behl et aL, 1994;Levine et al, 1994;Wu et al, 1995) and reflects the high K m of the enzyme. The water fractions were solubilized for 15 min at 22°C in sample buffer (Laemmli, 1970) and resolved by SDS-AGE.…”
Section: In Vitro Agp Cross-linkingsupporting
confidence: 89%
“…Biagi et al (2006) demonstrated that feeding gluconic acid positively influenced the composition and activity of the intestinal microflora of piglets after weaning. It has been reported that sustained oxidative stress through the maintenance of low concentration of H 2 O 2 by GOD's continued catalytic activity to be effective against pathogenic bacteria (Dobbenie et al, 1995;Wu et al, 1995). Etemadzadeh et al (1985) reported that the ability of GOD to kill Streptococcus mutans appears to be enhanced, because the H 2 O 2 produced by GOD acts as a useful bacteriocide.…”
Section: Resultsmentioning
confidence: 99%
“…The constitutive expression of an H202-generating glucose oxidase from Aspergillus niger in the apoplast of transgenic potato resulted in good resistance to the bacterial soft rot pathogen Erwinia carotovora sp carotovora and enhanced resistance to I? infestans (Wu et al, 1995). However, the mechanism underlying this general disease protection is not known.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%